Appointment Booking and Drug Inventory System in Healthcare Services Using Blockchain Technology - Sumathi, M.; Dhiraj, Inti; Mahita, Dhavala Sai; Raja, S. P. (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2023)
Blockchain technology has the potential to revolutionize the healthcare industry by improving data security, reducing administrative inefficiencies, and enabling the seamless sharing of medical information. In the healthcare sector, blockchain can be applied to a wide range of use cases, such as medical record-keeping, clinical trials, drug traceability, and telemedicine. By using a secure, decentralized system, healthcare organizations can ensure that sensitive patient data is kept confidential and can be easily accessed by authorized parties. Additionally, the use of smart contracts can contribute to reducing the risk of errors and saving time and resources. In the proposed work, a decentralized application integrates healthcare services with blockchain technology to ensure transparency and security and prevent tampering with electronic medical records. The three main functionalities implemented in this work are to provide a transparent appointment booking system where patients can view the real-time availability status of the doctors and book an appointment with the doctor of their choice, and to store and retrieve data in an efficient and secure manner. To maintain a transparent and tamper-resistant medical inventory to prevent the unauthorized sale of medicines and drugs and also verify the availability of the drug. This helps the patients get the drugs in the quickest manner possible. Compared to existing centralized storage techniques, the proposed decentralized storage technique provides higher data availability, the fastest response time, and immutable storage of existing data. Experimental results show that, compared to existing work, the proposed work provided better results in throughput and latency. The communication cost of the proposed technique is 7% lesser than the existing Telecare Medicine Information system.